2011
DOI: 10.1007/s00128-011-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Passerine Feathers to Evaluate Heavy Metal Pollution in Central Portugal

Abstract: In 2003, two sampling strategies were applied in order to evaluate metal contamination in passerine bird feathers. One strategy included the use of nest boxes and nestling great tits in a forest habitat (MU). The other strategy focused on the use of mist nets to capture adult blackbirds, robins and blackcaps in a fragmented non-forested habitat (EST). There was a significantly higher concentration of mercury in great tits (1.09 ± 0.40) sampled in MU and also in robins (3.44 ± 0.91) and blackcaps (1.62 ± 1.99) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Low level of mercury was measured in different countries. The detected amount of it was 1.86±0.51 mg/kg in great tits (Parus major) in Belgium (Janssens et al, 2002), 0.66± 0.68 mg/kg in rural area and 1.09±0.40 in forest habitat in passerines in Portugal (Costa et al 2011) and 383 μg/kg in cattle egret (Bubulcus ibis) in Bali (Burger and Gochfeld 1997). Also, it has been found that young chickens can tolerate 1.35 mg/kg diet (March et al 1983), but 5 mg/kg increases mortality (Soares 1973).…”
Section: Mercurymentioning
confidence: 96%
See 1 more Smart Citation
“…Low level of mercury was measured in different countries. The detected amount of it was 1.86±0.51 mg/kg in great tits (Parus major) in Belgium (Janssens et al, 2002), 0.66± 0.68 mg/kg in rural area and 1.09±0.40 in forest habitat in passerines in Portugal (Costa et al 2011) and 383 μg/kg in cattle egret (Bubulcus ibis) in Bali (Burger and Gochfeld 1997). Also, it has been found that young chickens can tolerate 1.35 mg/kg diet (March et al 1983), but 5 mg/kg increases mortality (Soares 1973).…”
Section: Mercurymentioning
confidence: 96%
“…Portuguese scientists have detected similar amount of it in passerine birds (2.23±1.18 mg/kg) (Costa et al, 2011). Szabó (1998) investigated the lead concentration of species of wildfowl's (Anseriformes) feather in Hungary.…”
Section: Leadmentioning
confidence: 99%
“…The current reported lead concentration in the avian feathers is below than the reported lead values of various scientists from Pakistan like Abdullah et al (2015), Malik and Zeb (2009) and Ullah et al (2014) as showen in Table 4. On the other hand the reported lead concentration is greater than the findings of Barbieri et al (2010); Costa et al (2011);Mansouri et al (2012); Costa et al (2013); Zarrintab et al (2016) from various parts of the world (Table 3). 2005).…”
Section: Leadmentioning
confidence: 58%
“…In Portugal the populations are located in Figueira da Foz (40 02 0 N, 8 52 0 W): the polluted zone is located at a 1 km distance from a pulp factory with a reference zone 20 km away. The main pollutants in Figueira da Foz are As, Cd, Cu, Hg, Ni, Pb, Se and Zn (Costa et al, 2012;Costa et al, 2011).…”
Section: Methodsmentioning
confidence: 99%